Cycles of conditional cooperation in a real-time voluntary contribution mechanism - M. Vittoria Levati; Ro'i Zultan (Games, 2011)
This paper provides a new way to identify conditional cooperation in a real-time version of the standard voluntary contribution mechanism. We define contribution cycles as the number of contributors a player waits for before committing to a further contribution, and use a permutation test on contribution cycles to assign a measure of conditional cooperation to each group play. The validity of the measures is tested in an experiment. We find that roughly 20% of the plays exhibit dynamics of conditional cooperation. Moreover, notwithstanding a decline in contributions, conditional cooperation is found to be stable over time.
Keywords: 330; public goods game; real-time protocol; information feedback; conditional cooperation